Precision Machining Technology, 3rd Edition - Peter J. Hoffman; Eric S. Hopewell (Cengage Learning, 2019)
Packed with detailed examples and illustrations, PRECISION MACHINING TECHNOLOGY, Third Edition, provides an ideal introduction to today's machine tool industry, equipping readers with a solid understanding of fundamental and intermediate machining skills. Aligned with the National Institute of Metalworking Skills (NIMS) Machining Level I Standard, the text can help readers achieve NIMS credentials. PRECISION MACHINING TECHNOLOGY carries NIMS' exclusive endorsement and recommendation for use in NIMS-accredited Machining Programs, and the Third Edition includes expanded coverage of CNC programming, updated images, and newly formatted multi-step procedures that are even easier to follow. The text continues to emphasize safety throughout, and it includes thorough coverage of a wide range of topics, including hand tool basics, job planning, benchwork, layout, drill press, lathe, milling, grinding, and CNC. Within the companion Workbook and Shop Manual, review material can help readers master key concepts, while guided practice operations and hands-on projects using a wide range of machine tools pave the way for NIMS credentialing success. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.